재외국재산의 정당한 시가감정기관해석문제 -상속세 및 증여세법을 중심으로 - 김기완; Ki Wan Kim; 한명수; Myung Soo Hahn (감정평가학 논집, 2011)
In the assessment of Korean assets abroad by Korean tax office the appraised value by the eligible appraisal organization is regarded as one of the standards either in identification or in calculation of The Market Value. However the detailed definitions of the organization vary with every tax law are unclear and in distinct. In principle, in Korea, the eligible appraisal organization shall be the one established in accordance with the Law of Public Announcement of Real Estate and Appraisal whether or not the assets are located at foreign countries as long as they belong to Korean tax payers regardless of a resident or a non-resident. In case when any exceptions may be necessary, such exceptions should be strictly stipulated in the law. Accordingly we suggest the reasonable and logical interpretation of currently confused clauses is essential. Further to the above, the immediate revision of such an inconsistent legal terms and clauses is a must.